Outcomes in Pediatric Thyroidectomy: Results From a Multinational, Multi‐institutional Database. (8th February 2022) - Maksimoski, Matthew; Bauer, Andrew J.; Kazahaya, Ken; Manning, Scott C.; Parikh, Sanjay R.; Simons, Jeffrey P.; D'Souza, Jill; Maddalozzo, John; Purkey, Matthew R.; Rychlik, Karen; Ho, Brian; Rutter, Michael J.; et al.
Abstract : Objective: Traditionally, data regarding thyroidectomy were extracted from billing databases, but information may be missed. In this study, a multi‐institutional pediatric thyroidectomy database was used to evaluate recurrent laryngeal nerve (RLN) injury and hypoparathyroidism. Study Design: Retrospective multi‐institutional cohort study. Setting: Tertiary care pediatric hospital systems throughout North America. Methods: Data were individually collected for thyroidectomies, then entered into a centralized database and analyzed using univariate and multivariable regression models. Results: In total, 1025 thyroidectomies from 10 institutions were included. Average age was 13.9 years, and 77.8% were female. Average hospital stay was 1.9 nights and 13.5% of patients spent at least 1 night in the pediatric intensive care unit. The most frequent pathology was papillary thyroid carcinoma (42%), followed by Graves' disease (20.1%) and follicular adenoma (18.2%). Overall, 1.1% of patients experienced RLN injury (0.8% permanent), and 7.2% experienced hypoparathyroidism (3.3% permanent). Lower institutional volume (odds ratio [OR], 3.57; 95% CI, 1.72‐7.14) and concurrent hypoparathyroidism (OR, 3.51; 95% CI, 1.64‐7.53) correlated with RLN injury on multivariable analysis. Graves' disease (OR, 2.27; 95% CI, 1.35‐3.80), Hashimoto's thyroiditis (OR, 4.67; 95% CI, 2.39‐9.09), central neck dissection (OR, 3.60; 95% CI, 2.36‐5.49), and total vs partial thyroidectomy (OR, 7.14; 95% CI, 4.55‐11.11) correlated with hypoparathyroidism. Conclusion: These data present thyroidectomy information and complications pertinent to surgeons, along with preoperative risk factor assessment. Multivariable analysis showed institutional volume and hypoparathyroidism associated with RLN injury, while hypoparathyroidism associated with surgical indication, central neck dissection, and extent of surgery. Low complication rates support the safety of thyroidectomy in pediatric tertiary care centers.